Brassinosteroid gene regulatory networks at cellular resolution in the Arabidopsis root - Nolan, Trevor M.; Vukašinović, Nemanja; Hsu, Che-Wei; Zhang, Jingyuan; Vanhoutte, Isabelle; Shahan, Rachel; Taylor, Isaiah W.; Greenstreet, Laura; Heitz, Matthieu; Afanassiev, Anton; Wang, Ping; Szekely, Pablo; et al. (Science (American Association for the Advancement of Science), 2023)
Brassinosteroids are plant steroid hormones that regulate diverse processes, such as cell division and cell elongation, through gene regulatory networks that vary in space and time. By using time series single-cell RNA sequencing to profile brassinosteroid-responsive gene expression specific to different cell types and developmental stages of the Arabidopsis root, we identified the elongating cortex as a site where brassinosteroids trigger a shift from proliferation to elongation associated with increased expression of cell wall–related genes. Our analysis revealed HOMEOBOX FROM ARABIDOPSIS THALIANA 7 ( HAT7 ) and GT-2-LIKE 1 ( GTL1 ) as brassinosteroid-responsive transcription factors that regulate cortex cell elongation. These results establish the cortex as a site of brassinosteroid-mediated growth and unveil a brassinosteroid signaling network regulating the transition from proliferation to elongation, which illuminates aspects of spatiotemporal hormone responses. Hormones known as brassinosteroids affect many aspects of plant growth and development. Nolan et al . applied single-cell RNA sequencing to the roots of the small mustard plant Arabidopsis to study how brassinosteroids control the developmental shift that cells undergo as they cease proliferation and begin to elongate. The gene network involved drove altered expression of genes involved in cell wall biogenesis and organization. Two particular transcription factors were identified as regulators of cell elongation. —PJH Single-cell RNA sequencing identifies the elongating root cortex as the site of brassinosteroid-dependent growth.